The Influence of Information Wealth in Tiktok Content on Increasing Cross-Cultural Knowledge: Survey of @iamegamei Followers regarding Diversity in India - Husaini, Laela Nuur; Hardiyanti, Rini; Abdurrahman, Ade Irfan (Institut Komunikasi dan Bisnis LSPR, 2024)
This research aims to determine the effect of the richness of information in @iamegamei content regarding diversity in India on increasing Followers' cross-cultural knowledge. This type of research is quantitative research with a positivism paradigm, data will be obtained using a questionnaire which will be distributed to 100 Followers of @iamegamei, samples determined based on the Slovin formula, then the data will be analyzed using IBM Statistics 25 Software. The results show that variable X and variable Y have values The significance is 0.000b and the hypothesis test value shows that the t-count value is 10,270 > t-table 1.987 and the significance is 0.000 < 0.05, which means that H0 is rejected and H1 is accepted. The results of the coefficient of determination test (R2) show that Information Wealth has an influence of 51.8% on increasing Cross-Cultural Knowledge of @iamegamei Followers, so it is concluded that Information Wealth in @iamegamei's TikTok content which discusses India's diversity has an influence on increasing Cross-Cultural Knowledge in among his Followers.